Determinants of Employee Performance: A Study on Compensation, Supervision, and Work Discipline - Fitria, Tri; Djazuli, Abid; choiriyah, choiriyah (Universitas Muhammadiyah Palembang, 2024)
This research aims to determine the effect of compensation, supervision and work discipline on The Performance Of PT Unicharm Indonesia Tbk Distributor Empoyees South Sumatera Province. The object of this research is a mining company listed on the Distirbutor employees south Sumatera province. The population in this study were 137 employee on the distributor of PT Unicharm Indonesia Tbk south sumatera province. With the number of samples obtained from 102 employee companies listed on the distributor employees of PT Unicharm Indonesia Tbk south sumatera province , the sampling method used the purposive sampling method. The analysis technique used was multiple linear regression with the help of the SPSS application. The results of this research show that compensation (X1) has no significant effect on performance (Y), while Supervision (X2) and work discipline (X3) have a significant effect on stock prices.